PENGARUH KEPEMIMPINAN TERHADAP KEDISIPLINAN PEGAWAI PT. PLN (PERSERO) - Harmita Harmita; Nurbiah Tahir; Burhanuddin Burhanuddin (Program Magister Ilmu Administrasi Publik, Universitas Muhammadiyah Makassar, 2022)
This study purposed to describe and explain the influence of leadership on the discipline of employees of PT. PLN (Persero) Tello Makassar City Generation Control Implementation Unit (UPDK). This study used descriptive quantitative to describe and analyze the magnitude of the influence of the leadership variable on the employee discipline variable. The sample of this study was 59 employees who were selected using the saturated sampling technique method from 59 members of the population. The results of descriptive statistical analysis showed that the picture of leadership was 47.15%, which meant that the leadership of PT. PLN (Persero) Tello Generation Control Implementation Unit (UPDK) Makassar City was categorized as not good and the description of employee discipline was 41, 33% which meant employee discipline at PT. PLN (Persero) Tello Makassar City Generation Control Implementation Unit (UPDK) was categorized as not good below 50%. The results of hypothesis testing (t test) found the t value of 2,351 t table 2,008 or the value of sig 0,022 smaller than 0,005, this indicated that Ha was accepted, which meant that there was a significant and positive influence between leadership and employee discipline.